PENGARUH EDUKASI MELALUI MEDIA VIDEO ANIMASI TERHADAP PENGETAHUN PADA REMAJA TENTANG BAHAYA MEROKOK DI SMPN 2 RANCAEKEK KABUPATEN BANDUNG (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: In 2017(WHO), there were 1.26 billion smokers, of which more than 200 million people were teenagers. According to the Minister of Health, at the tobacco conference held in Indonesia, more than a third of the population or 36.3% of the population in Indonesia are active smokers. Even 20% of them from the age of 13-17 years are smokers. Then the number of teenage boys who smoke increases from year to year. Knowledge is one of the factors that cause smoking behavior in adolescents. Teenagers at SMPN 2 Rancaekek have never been given education/counseling about the dangers of smoking. Objective: To determine the effect of education through animated video media on the knowledge of adolescents about the dangers of smoking at SMPN 2 Rancaekek, Bandung Regenc y. Method: Quasi-expression one group pretest posttest. The subjects of this study were 85 adolescents at SMPN 2 Rancaekek. Univariate analysis of mean and bivariate analysis with paired T-test. Results: The mean pretest 32.94 posttest 57.06 with an increase of 24.12. There is an effect of animated video on knowledge with a P value of 0.000 < 0.05. Conclusion: There is an effect of education through animated video media on knowledge of adolescents about the dangers of smoking at SMPN 2 Rancaekek, Bandung Re gency. Recommendation: It is hoped that this animated video media can be a source of information that can be utilized and disseminated by teachers and organizations in schools about the dangers of smoking.